"If she had broken her leg she would not have waited in agony for 9 months": Caregiver's experiences of eating disorder treatment. (22nd September 2020) - Robinson, Isabella; Stoyel, Hannah; Robinson, Paul
Abstract: This study aims to explore caregivers' experiences of eating disorder services and subsequent impacts on the caregiving burden and patient outcomes. Thematic analysis was employed to investigate qualitative data from a caregiver‐targeted online survey run by BEAT, the UK's largest eating disorder charity. Six hundred and 16 caregivers completed the survey. Participants' experiences of eating disorder treatment were predominantly negative, characterised by three main themes: (a) Barriers to care: enduring obstacles caregivers face in accessing support for their loved ones, (b) Experiences of services: high levels of unmet needs for caregivers and patients alike, (c) Affected domains: the pervasive impact of caregiving, influenced by experiences of services. This study is the largest of its kind to explore caregivers' experiences of eating disorder treatment services and aims to give voice to this overlooked group within research. Notably, little has been done to address broader systemic challenges faced by caregivers in accessing support for loved ones. Results indicate these challenges may play a substantial role in shaping the caregiving burden, carer coping styles, and subsequent patient outcomes. Findings denote wider systemic issues and a lack of specificities of information and practical skills that could help prevent caregivers from experiencing the caregiving burden and subsequent consequences on eating disorder patient outcomes.